MiR-148b-3p, as a tumor suppressor, targets son of sevenless homolog 1 to regulate the malignant progression in human osteosarcoma. Issue 2 (1st February 2022) - Liu, Guodong; Mao, Honggang; Liu, Yan; Zhang, Zun; Ha, Si; Zhang, Xiaoyan
ABSTRACT: Osteosarcoma (OS) is a malignant tumor that occurs in children and adolescents. Previous studies reported a low expression of miR-148b-3p in OS, but its biological function in OS remains obscure. This study aimed to explore the role of miR-148b-3p in OS progression. Herein, the expression of miR-148b-3p and son of sevenless homolog 1 (SOS1) both in OS tissues and cells were examined using quantitative real-time polymerase chain reaction and Western blotting assay. miR-148b-3p mimic or inhibitor, pcDH-SOS1 plasmid or si-SOS1 and agomir-miR-148b-3p were constructed for cell transfection. In vitro, the biological effect of miR-148b-3p was determined employing MTT, EdU, colony formation, flow cytometry, transwell and wound healing assay, separately. The target relationship between SOS1 3'-untranslated region (3'-UTR) and miR-148b-3p was analyzed using dual-luciferase reporter gene. In vivo, the inhibition of agomir-miR-148b-3p in mice was evaluated via a xenograft mouse model. miR-148b-3p was noticeably low-expressed in OS tissues and cells, and miR-148b-3p over-expression in OS cells suppressed the growth, migration and invasion, induced apoptosis. The effect of miR-148b-3p-inhibitor on cell biological behavior is opposite to that of miR-148b-3p over-expression. Conversely, The expression of SOS1 was significant higher in OS tissues and cells, miR-148b-3p targeted and was negatively associated with the expression level of SOS1. In addition, the anti-tumor effect of miR-148b-3p was reversed by SOS1. Importantly, we demonstrated that the tumor growth of stably over-expressed miR-148b-3p human MG-63 cells was obviously reduced in tumor-bearing mice. These data highlighted that miR-148b-3p might be as a promising therapeutic target for OS. Graphical abstract: uf0001